Physician Satisfaction in a Cancer Prevention Program for Low-Income Women in Nevada - Christopher R. Cochran; Emmanuel C. Gorospe (The Scientific World Journal)
Physicians and health care organizations that provide services to low-income patients are valuable partners in improving health care access for the uninsured and medically underserved. In this pilot study, we explored physicians' needs and factors for satisfaction in the Women's Health Connection (WHC), a breast and cervical cancer-screening program for low-income women in Nevada. Of the 126 physicians in the WHC program, 50 physicians completed a needs-and-satisfaction questionnaire. Survey data were subjected to factor analysis using Varimax rotation. The results yielded three components, which accounted for 65% of the variance. The three components or dimensions for physician satisfaction were: (1) appropriate administrative support and documentation, (2) availability of support for medical management, and (3) timeliness of diagnostic reports. Amount of reimbursement was not a significant factor. The respondents serving in this cancer prevention program for low-income women were satisfied in their involvement in the program. Further attention should be given on the identified issues for satisfaction among physicians, which could lead to quality improvement and serve as a model for other programs that serve low-income patients in cancer prevention.